Study on its application and unstable risk subarea estimation method of mountainous traffic engineering’s spoil ground - Jihong Zhang; Zhongji Dong; Xiaotao Yin; Min Yang (Frontiers in Earth Science)
Residues disposal areas with different quantities and scales are produced with the traffic engineering construction in mountainous areas construction, whose environment security threats need to be termly estimated. Countermeasures are adopted by estimated results, and safety risk management and control of waste dump engineering are realized. Based on field research and data access, stage characteristics of the process is summarized. Then force equilibrium and moving balance equation of waste dump sliding body at different stages are formed. So, risk grades and subarea labeled by red, yellow and green colors based on different moving distances are established. Finally, traditional way and the failure risk subarea assessment method are compared in practice, which proves feasibility of the method. Main conclusions are as following. 1) Fail process of mountainous highway waste slag slope is divided into initial limit equilibrium stage, speed-up downslide stage on slipping surface in which the sliding friction coefficient continues to decrease with acceleration, and speed-down downside stage on ground surface in which the sliding friction coefficient continues to increase with the deceleration. 2) Force balance equation at initial stage, downslide force formula at speed-up downslide stage and anti-slide force formula at speed-down downslide stage are presented by sliding body mechanical model on slipping surface and ground surface. Maximum moving velocity formula at the toe of the slope is established. And moving distance of waste dump sliding body is induced by energy balance equation. 3) Minimum and maximum of moving distance are computed under maximum and minimum of sliding friction coefficient conditions. According to these distances, safety threats of fail waste dump are classified into three grades: red region being high risk locates, yellow region being middle risk locates, green region being low risk. Relying on practical residues disposal area, disadvantage and advantage of the method and traditional method are compared. Found that mechanical mechanism of the method is simple, forces and parameters are all unified in balance equations, which meets to practical waste dump fail process. And the method does good to guiding mountainous residues disposal area unstable risk assessment.